SQ bisects RST, and RSQ = 2x-4. Write an expression for RST.
Slect an answer:
4x – 8
4x – 4
2x – 4
x – 2
![SQ bisects RST and RSQ 2x4 Write an expression for RST Slect an answer 4x 8 4x 4 2x 4 x 2 class=](https://us-static.z-dn.net/files/dd3/81ddc4f9b21363cb9baaf341b4841bdd.png)
Answer:
4x - 8
Step-by-step explanation:
... ∠RST = ∠RSQ + ∠QST
Since SQ bisects ∠RST, that means ...
... ∠RSQ = ∠QST
Using this fact in the first equation, we have
... ∠RST = ∠RSQ + ∠RSQ = 2×∠RSQ
Using the given expression for ∠RSQ, we have
... ∠RST = 2×(2x-4) = 4x - 8
4x - 8 ← first in list
Since SQ bisects ∠RST then ∠RSQ = ∠QST = 2x - 4
∠RST = ∠RST + ∠QST
∠RST = 2x - 4 + 2x - 4 = 4x - 8